Perancangan Sistem Informasi Manajemen Pendaftaran Pasien Rawat Jalan Berbasis Web Di RSKIA Permata Bunda Yogyakarta: Grafik Pelaporan, Cetak Kartu Identitas Berobat Dan Kuitansi Pembayaran - Hendra Rohman; Dyah Evanka Nur Ikhsani (HB PRESS, 2020)
RSKIA Permata Bunda established a medical record system was manual system. Outpatient registration using outpatient register. If patient returns to treatment, the officer encounters difficulties when searching for the patient's medical record number. The risk of duplication of medical record numbers occurs, when there were patients who do not carry medical identity cards, the officer has difficulty knowing patients who have previously treated or not. Duplicating medical record causes patient data become separate. Reporting data using microsoft excel. This study aims to produce an outpatient data processing information system that faster and effective. Prototype design method as a method for developing web based management information systems. Data collection techniques using purposive sampling. As a result, the existence of a web based outpatient registration information system can facilitate officers in managing patient data, including data input in the registration process, recording medical records of patients, recording doctor data, recording clinical data, patient visit reports and can print identity cards for patient medication and payments. In conclusion, based on the results of needs analysis, design and implementation, this system can help, make it easier for officers to process patient data, make reporting graph, medical identity card and receipt of payment.